Molecular and Cellular Mechanisms Underlying Recurrent Urinary Tract Infections Caused by Pseudomonas aeruginosa in Women - Lina A. Naser (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Recurrent urinary tract infections (rUTIs) in women represent a persistent clinical problem with substantial healthcare burden and frequent relapse episodes. Specific Background: Pseudomonas aeruginosa has emerged as an opportunistic uropathogen characterized by advanced molecular and cellular strategies, including quorum sensing, biofilm formation, virulence factor expression, and intracellular persistence within bladder epithelial cells. Knowledge Gap: Despite increasing recognition of its role, the precise mechanisms underlying persistence and recurrence, particularly host–pathogen interactions and immune dysregulation, remain incompletely understood. Aims: This narrative review aims to synthesize current evidence on the molecular and cellular pathways driving recurrent infections caused by P. aeruginosa in women. Results: The findings highlight interconnected mechanisms, including quorum sensing systems (Las, Rhl, Pqs), biofilm-mediated protection, secretion systems (Type III and VI), intracellular reservoirs, and altered innate immune responses involving Toll-like receptors and inflammasomes, alongside host-related factors such as hormonal and genetic influences. Novelty: This study integrates microbiological, immunological, and clinical perspectives into a unified framework explaining recurrence dynamics. Implications: Improved understanding of these mechanisms provides a foundation for identifying therapeutic targets and guiding the development of strategies to prevent recurrence and improve clinical management of rUTIs in women. Highlights:• Intracellular Bacterial Reservoirs Enable Persistence and Relapse After Apparent Clearance• Coordinated Signaling Systems Regulate Virulence Expression and Adaptive Survival Strategies• Host Immune Dysregulation and Hormonal Factors Contribute to Susceptibility in Female Patients Keywords: Pseudomonas Aeruginosa, Recurrent Urinary Tract Infections, Biofilm Formation, Quorum Sensing, Host Pathogen Interactions